FAKTOR – FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM KEPUTUSAN PEMBELIAN BUAH DI FRESHMART TIKALA KOTA MANADO - Melisa Ekawati Sugiarto; Ribka M. Kumaat; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2017)
The study aims to identify factors - factors that affect consumer purchasing decisions of fruit in Freshmart Tikala, Manado based on aspects of individual consumers, environmental influences and marketing strategies. This study is a qualitative research with quantitative approach. The research was conducted from September to December 2016 in Freshmart Tikala, Manado. The data used are primary data obtained through interviews with 60 respondents who have bought fruit in October 2016. The sampling method is to use accidental sampling method. Analysis of the data used consisted of a questionnaire test, classic assumption test, descriptive analysis, regression test, determination test, F test and t test. These results indicate the test results of multiple regression analysis is positive and significant F-test value <0.05, which means simultaneously independent variables affect the dependent variable. The results of t test analysis of individual consumer variables, environmental influences and marketing strategies significant value <0.05 means that the independent variable (the individual consumer, environmental influences, and marketing strategies) partially influence on purchasing decisions. The variable most influential in purchasing decisions is variable marketing strategy that has the highest coefficient of 0,243 and 0,000 significant value. Thus the individual consumer factors, environmental influences and marketing strategy and a significant positive influence in decisions on buying fruit.Keywords: consumer, purchasing decisions, fruit, Freshmart, Tikala, Manado